Statistics, an introductory analysis - Yamane, Taro. (New York : Harper & Row, 1964)
This book is mainly for students in business and economics but it has also been designed so that with appropriate selections of chapters it may be used by students in other disciplines. The authors also adopted that in college, the main emphasis should be on the theoretical aspects of statistics, that is, the emphasis should be on the "why" rather than the "how". Hypothetical examples have been used and deliberately kept simple so that the statistical process does not become submerged in a jungle of calculations.
Includes index.
aia 23/08/2018
Loans
Keywords: Statistics